IgA Complexes Induce Neutrophil Extracellular Trap Formation More Potently Than IgG Complexes - Gimpel, Anna-Katharina; Maccataio, Antonio; Unterweger, Harald; Sokolova, Maria V.; Schett, Georg; Steffen, Ulrike (Frontiers in Immunology, 2022)
Neutrophil extracellular trap (NET) formation is a powerful instrument to fight pathogens, but may induce collateral damage in the affected tissues. Besides pathogen-derived factors, immune complexes are potent inducers of NET formation. Neutrophils express IgA and IgG specific Fc receptors (FcRs) and therefore respond to complexed IgA and IgG. Especially in the context of autoimmune diseases, IgA and IgG immune complexes have been shown to trigger NET formation, a process that putatively contributes to disease severity. However, it is of question if both antibody classes stimulate neutrophils to the same extent. In this study, we compared the capability of IgA and IgG complexes formed by heat aggregation to induce NET formation. While stimulation of neutrophils with IgA complexes robustly induced NET formation, complexed IgG only marginally increased the amount of NETs compared to the unstimulated control. Mixing IgA with IgG before heat aggregation did not increase the effect of complexed IgA on neutrophils. By contrast, the presence of IgG complexes seemed to disturb neutrophil stimulation by IgA complexes. The capacity of complexed IgG to induce NET formation could not be increased by the addition of autologous serum or the removal of terminal sialic acid in the Fc glycan. Together, our data show that IgA is a much more potent inducer of NET formation than IgG. IgA may thus be the main driving force in (auto)immune complex-mediated NET formation.